Free Agency, Long-Term Contracts and Compensation in Major League Baseball: Estimates from Panel Data - Kahn, Lawrence M. (The Review of Economics and Statistics, 1993)
Using longitudinal data for major league baseball players, this paper estimates the effects of eligibility for free agency or arbitration on compensation and contract duration. Becaus e eligibility is based on experience and better players are kept longe r, a fixed effects approach is used. Arbitration and free agency eligibility both raised annual compensation; however, only free agen cy raised contract duration. The free agency findings are consistent wi th Nash bargaining; however, additionally considering the arbitration results suggests the "winner's curse": duration rises only when a team might lose a player. The auction market is thus avoided. Copyright 1993 by MIT Press.